Interdisciplinary treatment of ectodermal dysplasia with oligodontia: review and case report - Čedomir Oblak; Maja Ovsenik; Nataša Ihan Hren (Zdravniški Vestnik, 2013)
Background: Ectodermal dysplasia (ED) is a group of hereditary diseases with disorders in the development of two or more ectodermal structures, such as hair, teeth, nails and sweat glands. The symptoms of craniofacial anomalies express themselves with a larger number of unerupted teeth – oligodontia. Facial characteristics appear because of disorders in the growth of facial bones due to congenitally missing teeth related to underdeveloped alveolar ridge. Treatment planning in these patients requires interdisciplinary approach, and should include various possibilities of substitution of congenitally absent teeth, orthodontic treatment, orthognatic surgery, skeletal augmentation, surgical insertion of dental implants, prosthetic rehabilitation and genetic counseling. Case presentation: In a patient with ectodermal dysplasia, clinical examination and analysis of panoramic x-ray revealed 17 congenitally absent permanent teeth with extensive atrophy of the alveolar ridge, hypotrichosis, narrow face, prominently expressed chin with speech and mastication difficulties. Rehabilitation planning included an extensive interdisciplinary approach with orthodontically guided three-dimensional correction of the upper and lower jaw relationship that was followed by a surgical open lift of the sinus floor on the right side and insertion of four dental implants. In the mandibular arch, the missing teeth were replaced with a metal-porcelain bridge on the supporting teeth and with two bridges supported on the dental implants in the maxillary arch. After 12 years of interdisciplinary treatment the patient was successfully rehabilitated. Conclusion: Treatment of patients with ectodermal dysplasia and oligodontia is individual and must be targeted mainly at prevention, for it is necessary to conserve the patient’s own teeth and at the same time replace (the) missing tissues and teeth, and correct the facial structures.